Analisis Dan Perancangan Sistem Informasi Manajemen Sumber Daya Manusia Di Era Digital - Marsya Alsabila; Muhammad Irwan Padli Nasution (CV. SINAR HOWUHOWU, 2026)
Almost every element of life has changed as a result of the development of digital technology, including how companies handle their human resources. In today's economic environment, information systems for human resource management are essential because they assist firms manage data, increase efficiency, and enable more precise decision-making. This article provides a thorough discussion on the analysis of demands and the design of pertinent HR information systems in the digital age by looking at how technologies like cloud computing, data analytics, and artificial intelligence help human resource management. This study uses a qualitative methodology by reviewing prior research and the application of HR information systems in different industry sectors. Research indicates that, in addition to the technology employed, business culture, sound governance, and human resource preparedness all influence how successfully HRM information systems are adopted. The study's conclusion emphasizes how crucial integrated, data-driven, and adaptable HR information systems are to assisting companies in meeting the demands of the digital age.